Pengaruh Influencer Credibility, Customer Experience dan Customer Loyalty Terhadap Brand Trust (Potato Kriwil) di Kota Bengkulu - Fitri Andriyani; Syofian Syofian; Arifah Hidayati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to determine the effect of influencer credibility, customer experience, and customer loyalty on brand trust (Potato Kriwil) in Bengkulu City. The method used in this study is explanatory (explanatory research). The results of the study indicate that influencer credibility, customer experience, and customer loyalty have a significant effect on brand trust (Potato Kriwil) in Bengkulu City (F-count > F-table). Customer Loyalty (X3) provides the greatest contribution to Brand Trust compared to the other two variables, although it is still in the small effect category but is approaching medium (0.134). In conclusion, influencer credibility, customer experience, and customer loyalty have a significant effect on brand trust (Potato Kriwil) in Bengkulu City. Suggestions: Further research is recommended to add other variables that also have the potential to influence brand trust, such as brand image, perceived value, or customer satisfaction, to a more comprehensive understanding.